Impact of External Debt on Economic Growth Rate: An Empirical Evidence from Pakistan - Zafar, Rabia; Zafar, Muhammad Maleeq-Ul-Islam (Technium Social Sciences Journal, 2022)
The major objective of this study is to check the effect of external debt on the GDP growth of Pakistan. For this purpose annual time series data were used for the period 1980 to 2020. Augmented Dickey-Fuller test was applied to check the stationary status of the data and the least square method was applied for the estimation of the results. For the analysis GDP growth rate was taken as a dependent variable and other variables, such as economic growth (Annual %), inflation rate (CPI %), Foreign Direct Investment net inflow (% of GDP), multi-lateral debt services (% of public and publically generated debt service), Total debt service (% of GNI), Short term debt (% of total reserves) were taken as explanatory variables. Findings revealed that the total debt and multilateral debt negatively affect the GDP growth rate, whereas, FDI and short term debt are positively associated with growth rate. It is suggested that to improve the economic growth Pakistan should focus on investment projects and there is a need to implementation better policies for foreign debt utilization